A Review Paper on Botnet and Botnet Detection Techniques in Cloud Computing - Shahid, Anwar; Jasni, Mohamad Zain; Mohamad Fadli, Zolkipli; Zakira, Inayat (IEEE, 2014)
Recently, botnets are the most radical of all cyberattacks and becoming the key issue in cloud computing. Botnets are the network of different compromised computers and/or smartphones. These devices are infected with malicious code by botmaster and controlled as groups. The attackers use these botnets for criminal activities such as DDoS, click fraud, phishing, spamming, sniffing traffic and spreading new malware. The main issue is how to detect these botnets? It becomes more interesting for the researchers related to cyber-security? This motivates us to write a review on botnets, its architecture and detection techniques.